City tales: growing up - Rumana, Husain (Oxford University Press Karachi, 2016)
This is a series of bilingual books with an urban theme. Children will get a glimpse of city life through the various stories. The central characters in the series are two sisters, Sonia and Anya. Sonia and Anya like to play together but sometimes there is a disagreement. In this story they have an argument while playing with building blocks. Father and Mother try to find an agreeable solution.